2013
DOI: 10.2139/ssrn.2278864
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Parental Health Shocks on Children's Non-Cognitive Skills

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Previous research has identified health shocks occurring to parents or other family members as important predictors of child development (Morefield et al, 2011, Adda et al, 2012, Westermaier et al, 2013, and Ryan and Anna, 2015. These shocks might also limit the time parents can spend with their children.…”
Section: Validity Of the Instrumental Variable Estimationmentioning
confidence: 99%
“…Previous research has identified health shocks occurring to parents or other family members as important predictors of child development (Morefield et al, 2011, Adda et al, 2012, Westermaier et al, 2013, and Ryan and Anna, 2015. These shocks might also limit the time parents can spend with their children.…”
Section: Validity Of the Instrumental Variable Estimationmentioning
confidence: 99%